2022
DOI: 10.1101/2022.11.16.515599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing of 2,023 colorectal cancers reveals mutational landscapes, new driver genes and immune interactions

Abstract: To characterise the somatic alterations in colorectal cancer (CRC), we conducted whole-genome sequencing analysis of 2,023 tumours. We provide the most detailed high-resolution map to date of somatic mutations in CRC, and demonstrate associations with clinicopathological features, in particular location in the large bowel. We refined the mutational processes and signatures acting in colorectal tumorigenesis. In analyses across the sample set or restricted to molecular subtypes, we identified 185 CRC driver gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…While STAG2 has a high mutational burden in normal tissue and lower in cancer, compared to the other tumour suppressor genes, SMAD4 has the opposite phenotype of lower mutational burden in normal tissue but enrichment in CRC. Recent studies reconstructing the timing of CRC events assign SMAD4 mutation to a late stage of progression as it is predominantly found to be subclonal (Gerstung et al ., 2020; Cornish et al ., 2022). Despite this, the occasional presence of truncal SMAD4 mutations might be indicative of a weak driver which relies on additional synergising events for transformation but does not employ a probabilistic strategy of increasing its tissue representation for co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…While STAG2 has a high mutational burden in normal tissue and lower in cancer, compared to the other tumour suppressor genes, SMAD4 has the opposite phenotype of lower mutational burden in normal tissue but enrichment in CRC. Recent studies reconstructing the timing of CRC events assign SMAD4 mutation to a late stage of progression as it is predominantly found to be subclonal (Gerstung et al ., 2020; Cornish et al ., 2022). Despite this, the occasional presence of truncal SMAD4 mutations might be indicative of a weak driver which relies on additional synergising events for transformation but does not employ a probabilistic strategy of increasing its tissue representation for co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis identified likely ancestral amplifications involving two canonical oncogenes in CedBTN1: MDM2 (10-13 copies; mean CN=10.9; gene CN percentile=98.3), encoding an important inhibitor of tumour suppressor proteins, and CCND3 (8-18 copies; mean CN=10.7; gene CN percentile=98.2), encoding a cyclin that promotes G1/S cell cycle transition (Supplementary Data 14). Recurrent amplification of these genes has been observed in multiple cancer types, and is thought to prevent cell cycle arrest and apoptosis under conditions of genomic instability [47][48][49][50][51][52] . In CedBTN2, we found evidence of a likely ancestral MYC amplification (7-11 copies; mean CN=9.2; gene CN percentile=96.3; Supplementary Data 14).…”
Section: Pervasive Genomic Instability Drives the Evolution Of Cockle...mentioning
confidence: 99%
“…mutations that reduce the immune system's ability to engage with neoantigens) has been thoroughly investigated and found to be common in CRCs 4,13 . Our previous mathematical modelling found that escape is essential for MMRd CRC development, and is a crucial step in MMRp CRC formation when immune surveillance is stringent 4,8,14 . The role of the epigenome in modulating tumour antigenicity, however, has received less attention: somatic changes in chromatin organisation are known to contribute to the cancer immunophenotype, but their impact on immune escape and editing have not been completely assessed [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancers (CRCs) generally display a relatively active immune microenvironment with substantial tumour-infiltrating lymphocytes 2 . About 15% of CRCs are mismatch repair deficient (MMRd), which is associated with a higher neoantigen burden, enhanced immune presence 3,4 and good response to immune checkpoint blockade therapies (ICBs), however, still up to 30% of MMRd CRCs do not respond 5 . Mismatch repair proficient (MMRp) CRCs harbour a lower mutation burden than MMRd CRCs and ICB treatments are ineffective 6 , indicating that immune evasion in MMRp tumours likely occurs through mechanisms alternative to those targeted by current ICB drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation